Inequality and Defined Benefit Pensions when Life Expectancy is Heterogeneous - Daniel Kemptner; Peter Haan; Victoria Prowse (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In this paper, we analyze how life expectancy-driven redistribution of income through a defined pension benefit system impacts on inequality in annual consumption. Our analysis combines a methodology that quantifies life expectancy-driven redistribution through the pension system with a structural life-cycle model in which labor supply, retirement and consumption decisions respond to changes in the pension system. Based on the estimated model, we show that the German pension system induces a large regressive redistribution of life-time income, and this redistribution increases inequality in average annual consumption. Behavioral responses to the pension system matter for the results. Increasing progressivity in pension contributions or pension benefits only partially offsets the life expectancy-driven redistribution via the pension system.
Keywords: C61; D31; H55; 330